Identifying factors associated with low back pain among employees working at a package producing industry - Yildirim, Yucel; Gunay, Sevtap; Karadibak, Didem (Ios Press, 2014)
BACKGROUND: The purpose of this study was to identify factors associated with Low Back Pain (LBP) among employee working at a package producing industry. METHODS: A sample of 111 male blue-collar workers, between the ages of 18 to 50 years old and 31 white-collar workers between the ages of 17 to 50 years old completed a questionnaire which included demographic data, educational level, participation in sports activities, activity, postural habits, smoking, work conditions lifting and bending activities during the workday strenuous arm position and questions related with low back pain (LBP). The isometric strength of back muscles were measured using a dynamometer. RESULT: The prevalence of LBP during the past 12 months was 55.9% for blue-collar workers and 51.6% for white-collar workers. The chi-square and t-test analysis showed statistically significant relations between LBP and smoking, number of years spent working in the last job, lifting activities between the ages of 30-34 years old. The incorrect standing and sitting posture of the blue-collar workers and the sitting posture with bending forward on the table of the white-collar workers were significantly related with LBP (p < 0.05). CONCLUSIONS: Our results identified the risk factors of LBP in a package producing company. The protective approaches aiming to avoid the risk factors could decrease the low back pain prevalence that increases each year passed worked at the company.
Keywords: Low back pain; risk factors; ergonomics